Eficácia de extratos vegetais na desinfecção de superfícies contaminadas com fungos do complexo Sporothrix - Matos, Caroline Bohnen de (2014)
Sporotrichosis is the main domestic feline ringworm, highly relevant because it is a zoonosis involving six fungal species belonging to the Sporothrix complex. The fungal isolation of home and veterinary environments has been proven, proving to be an important source of infection for animals and humans. The search for alternative to disinfectants commonly used products is increasing, mainly by continuing reports of resistance by microorganisms. The Origanum vulgare and Rosmarinus officinalis stand out because they have proven antimicrobial activity. Given the above, the objective of the study was to evaluate the efficacy of disinfectants and plant extracts in eliminating the fungus Sporothrix complex, and report a case of multifactorial dermatitis in a dog. For this, in vitro tests were performed using the technique of direct exposure to evaluate the action of the tincture, aqueous extract and alcoholic extract of O. vulgare and R. officinalis against clinical isolates of dogs and cats with sporotrichosis. Subsequently, the plant extracts that showed better results in the direct exposure test were evaluated for the elimination of Sporothrix spp different contaminated surfaces, also using different disinfectants. As an experimental model surfaces of stainless steel, formica and ceramic tile floors, tested in quadruplicate using the technique of spray-wipe-spray were used. According to the study, the hydroalcoholic extract and tincture of O. vulgare and R. officinalis were effective in eliminating the fungus Sporothrix complex, with no difference from the area used, including showing better results when compared to commercial products used.